The Impact of Liquidity, Nim, and Capital Structure on the Profitability of Banking Companies - Lelia Astriani; Retno Indah Hernawati (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This research seeks to examine the impact of liquidity, Net Interest Margin (NIM), and capital structure on the profitability of banking companies traded on the Indonesia Stock Exchange during the years 2022–2024. The method of research employed is quantitative, utilizing multiple linear regression approach derived from secondary information found in company financial reports. The research sample consisted of 24 banking firms consisting of a total of 70 data points. The findings of the analysis indicate that Net Interest Margin has a meaningful and positive impact on profitability, while liquidity and capital structure do not produce a notable impact. These results suggest that the efficiency of managing productive assets and net interest income are the main factors in increasing bank profitability, while liquidity management and capital composition have not contributed significantly to profit growth. This study has important implications for bank management to optimize NIM as the main strategy for improving financial performance, as well as for regulators and stakeholders in conducting evaluations and decision-making. This study also suggests expanding the variables and research period in the to acquire a more thorough insight into the factors that affect the profitability of banking companies.